Literature And Family Development: A Character Building Education (Journal of Namibian Studies : History Politics Culture, 2023)
This research intends to measure the extent of the relationship between family development and literature from a character building education perspective. The objectives of this research are formulated as follows: 1) reveal children literature's contribution as one of the family development aspects, 2) how parents provide character education to their children, and 3) parents' perceptions of children literature as an alternative media in shaping children's character. The results of this research show that children's literature can be an alternative medium in developing children's character. The social implication of this research is that through reading literature, children will learn moral education, socialize easily, have empathy for others, respect their parents, and have broad insight.